PENGARUH MODEL PEMBELAJARAN DISCOVERY LEARNING TERHADAP HASIL BELAJAR BAHASA INDONESIA KELAS V SD NEGERI 165 PALEMBANG - Resi Apriza; Rizhardi, Rury; Hermansyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The low learning outcomes of Indonesian language among fifth-grade students of State Elementary School 165 Palembang encourage the need for the application of innovative learning models. This research aims to determine the effect of the Discovery Learning model on the learning outcomes of Indonesian language for fifth-grade students at State Elementary School 165 Palembang. The method used in this study is a quantitative experimental method with a Quasi Experimental Design, utilizing a Nonequivalent Control Group Design. The data collection technique used is essay tests, consisting of pretests and posttests. The analysis results show that there is a significant difference in learning outcomes between the experimental class and the control class, with a (2-tailed) value of 0.001 < 0.025, thus it can be concluded that the Discovery Learning model has a positive effect on students' learning outcomes in Indonesian language subjects. Therefore, the application of the Discovery Learning model can enhance learning outcomes fifth grade students of State Elementary School 165 Palembang.